Water infiltration study on slopes / Low Tian Huat - Low, Tian Huat (2001)
study was carried out in the field using infiltrometer and in the laboratory using “sprinkler model”. Studies on infiltration have always been part of hydrology and Irrigation engineering. Infiltration forms the link between surface and subsurface hydrology. Infiltrated water must be quantified and subtracted from the surface runoff in flood prediction studies and surface water management. Numerous researchers have actually incorporated infiltration into the slope stability analysis of the residual soils, e.g., Othman (1990), Affendi et. al.(1992, 1996) and Suhaimi and Abdul Rahman (1997). In most analysis of slope stability, the infiltration rate of the slopes is assumed uniform throughout the slope. The soil is also assumed homogeneous except some layered bedding problem. Anderson et. al. (1985, 1988) in the United Kingdom, described the development of a combined soil-water slope stability model which incorporates infiltration in slope stability analysis. In tropical regions, most of the soils are residual soils and indirectly the slopes will normally cut through the residual soils and exposed all the difference weathering grades materials. The effects of the weathering grades on the infiltration rate are also discussed in detail.